Implementation of a Vital Sign Alert System to Improve Outcomes. Issue 4 (October 2019) - Huff, Shelly; Stephens, Kimberly; Whiteman, Kimberly; Swanson-Biearman, Brenda; Mori, Candy
Abstract : Background: Patients at risk for clinical deterioration often show changes in vital signs up to 24 hours before a critical event. Use of modified early warning scores has demonstrated effectiveness in identifying patients at risk for clinical deterioration and improving outcomes. Local Problem: Documentation of vital signs, timely recognition of clinical deterioration, and compliance with the sepsis bundles remained a challenge. Methods: An interprofessional team developed an electronic vital sign alert (VSA) system with a concurrent running sepsis screen, along with clinical protocols. Interventions: Education was provided and the VSA system was implemented on 3 nursing units. Results: After implementation, the number of unplanned transfers to the intensive care unit increased. Mortality rate and length of stay in the intensive care unit for patients transferred for respiratory failure and sepsis significantly decreased. There was a 21% increase in identification of sepsis. Conclusions: The VSA system was an effective tool to identify patients at risk for clinical deterioration and help to improve outcomes. Abstract : Supplemental Digital Content is Available in the Text.